Differences in Signal Activation by LH and hCG are Mediated by the LH/CG Receptor’s Extracellular Hinge Region - Grzesik, Paul; Kreuchwig, Annika; Rutz, Claudia; Furkert, Jens; Wiesner, Burkhard; Schuelein, Ralf; Kleinau, Gunnar; Gromoll, Joerg; Krause, Gerd (Frontiers in Endocrinology, 2015)
The human lutropin/choriogonadotropin receptor (LHCGR) can be activated by binding two slightly different gonadotropic glycoprotein hormones, choriogonadotropin (CG) - secreted by the placenta, and lutropin (LH) - produced by the pituitary. They induce different signaling profiles at the LHCGR. This cannot be explained by binding to the receptor's leucine-rich repeat domain (LRRD), as this binding is similar for the two hormones. We therefore speculate that there are previously unknown differences in the hormone/receptor interaction at the extracellular hinge region, which might help to understand functional differences between the two hormones. We have therefore performed a detailed study of the binding and action of LH and CG at the LHCGR hinge region. We focused on a primate-specific additional exon in the hinge region, which is located between LRRD and the serpentine domain. The segment of the hinge region encoded by exon10 was previously reported to be only relevant to hLH signaling, as the exon10-deletion receptor exhibits decreased hLH signaling, but unchanged hCG signaling. We designed an advanced homology model of the hormone/LHCGR complex, followed by experimental characterization of relevant fragments in the hinge region. In addition, we examined predictions of a helical exon10-encoded conformation by block-wise polyalanine (helix supporting) mutations. These helix preserving modifications showed no effect on hormone induced signaling. However, introduction of a structure-disturbing double-proline mutant LHCGR-Q303P/E305P within the exon10-helix has, in contrast to exon10 deletion, no impact on hLH, but only on hCG signaling. This opposite effect on signaling by hLH and hCG can be explained by distinct sites of hormone interaction in the hinge region s. In conclusion, our analysis provides details of the differences between hLH- and hCG-induced signaling that are mainly determined in the L2-beta loop of the hormones and in the hinge region of the receptor